(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
John Steinbeck’s The Grapes of Wrath remains a landmark of American literature for its powerful depiction of ecological catastrophe and its profound examination of the human spirit. Set against the backdrop of the Dust Bowl and the Great Depression, the novel dramatizes the struggle of displaced families, particularly the Joads, as they migrate westward in search of survival and dignity. This article explores the dual themes of environmental despair and human resilience, emphasizing how Steinbeck combines naturalistic detail with social commentary to portray a world of hardship and hope.